Respuesta :
Answer:
Perfect square trinomial:
(a – b)2 = (a – b)(a – b) = a2 – 2ab + b2
Find the product of (k – 9)2 using the perfect square trinomial rule shown on the left.
The product (k – 9)2 can also be written as
✔ (k – 9)(k – 9)
.
The product is k2 –
✔ 18
k +
✔ 81
.
Step-by-step explanation:
The expression in perfect square trinomial can be written as [tex](k-9)^{2}=(k-9)(k-9) =k^{2}-18k+81[/tex]
What is an algebraic expression?
An expression which is made up of variables and constants, along with algebraic operations (addition, subtraction, etc.). Algebraic expressions include at least one variable and at least one operation.
For the given situation,
Perfect square trinomial is [tex](a - b)^{2} = (a -b)(a -b) = a^{2} -2ab + b^{2}[/tex]
The expression is [tex](k-9)^2[/tex]
Based on the perfect square trinomial, the expression can be written as
⇒ [tex](k-9)^{2}=(k-9)(k-9) =k^{2}-2(k)(9)+9^{2}[/tex]
⇒ [tex](k-9)^{2}=(k-9)(k-9) =k^{2}-18k+81[/tex]
Hence we can conclude that the expression in perfect square trinomial can be written as [tex](k-9)^{2}=(k-9)(k-9) =k^{2}-18k+81[/tex]
Learn more about algebraic expression here
https://brainly.com/question/19245500
#SPJ2